Jazyk a styl De educatione juventutis - Belejčáková, Zuzana; Kosek, Pavel, 1972-; Masarykova univerzita. Ústav českého jazyka (2007)
Diplomová práce se zabývá jazykovým a stylovým rozborem barokní památky nízkého stylu „De educatione juventutis“ (1715) od Jana Ignáce Libertina (1689-1756). Dílo psané ve formě dialogu zobrazuje pravidla společenské etikety určené mladým chlapcům. Na základě hláskové, morfologické, syntaktické a lexikální analýzy textu je charakterizován celkový styl památky. Práce zachycuje také pravopisnou podobu textu. Při stylovém rozboru památky autorka popisuje dobově běžné i textově specifické prostředky, které srovnává s jejich odrazem v gramatikách Konstance, Šteyera a Rosy a v překladu Bible svatováclavské
This thesis attempts at a linguistic and stylistic analysis of a baroque low-brow literary work “De educatione juventutis“ (1715) by Jan Ignác Libertin (1689-1756). This text, written in a form of dialogue, shows the rules of etiquette, and is aimed at young boys. The complex characteristic of the text is delivered through phonological, morphological, syntactic and lexicological analysis. The thesis also deals with the orthographical form of this particular Libertin’s work. The author of this thesis gives a detailed description of both common and rare means of the text and compares them to how they were used and portrayed in the contemporary grammars by Konstance, Šteyer,Rosa and in the translation of St. Wenceslas’ Bible
Vedoucí práce: Pavel Kosek
Diplomová práce (Mgr.)--Masarykova univerzita, Filozofická fakulta, 2007
Keywords: Libertin, Jan Ignác, -- 1689-1756; 18. století; katoličtí kněží -- Česko -- 18. století; katechismy -- jazykové aspekty -- 18. století; Catholic priests -- Czechia -- 18th century; catechisms -- linguistics aspects -- 18th century; diplomové práce; master's theses